Factors related to sexual knowledge among Malaysian adolescents - Yaacob, Siti Nor; Wong, Fui Ping; Baharuddin, Rozumah; Mansor, Mariani; Juhari, Rumaya; Abu Talib, Mansor (Fakulti Pengurusan, Universiti Teknologi Malaysia, 2010)
This influence of gender, race, age and personal belief on adolescent’s sexual knowledge was examined. The respondents for the study were 860 school–going adolescents aged 13 to 18 from urbanization city in Peninsular Malaysia. Data were collected by using self-administered questionnaire. A cultural sensitive sexual knowledge scale was developed and employed to measure respondent’s sexual knowledge. Descriptive, bivariate and multiple statistical tests were conducted to examine the relationships between gender, race, age and personal belief with adolescents’ sexual knowledge. Findings of the present study showed that: 1) No significant mean difference in sexual knowledge between boys and girls. 2) There was a statistically significant difference in the mean of sexual knowledge among the three races (F (2,766) =14.84, p≤.001). 3) Respondents with higher score in sexual knowledge tend to be older (r=.21, p≤.05), have lower score on extent of living a life according to the religious belief (r=-.07, p≤.05), have lower self-perceived importance of religion in life (r=-.11, p≤.01), have higher self-perceived sexual openness (r=-.31, p≤.01) and have more positive attitude toward sex related sources (r=.35, p≤.01). Findings of this study will help to further improve the understanding of adolescents’ sexual knowledge and to give inputs to programs on adolescent development specifically in sexuality and reproduction health.